PENGGUNAAN BAHASA NON VERBAL DAN ETIKET KOMUNIKASI DALAM INTERAKSI PROFESIONAL PADA LINGKUNGAN KERJA KULINER UNTUK MENDUKUNG PENGEMBANGAN PARIWISATA - Raudah, Siti; Simarmata, Nada Farisya; Nurubay, Dayang Nisyrina; Fahmi, Muhammad; Maldin, Siska Amelia (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2025)
This study examines the role of nonverbal language and communication etiquette in professional interactions within culinary work environments. Using a literature review approach, the study identifies that nonverbal communication, such as facial expressions, body posture, and hand gestures, as well as the implementation of communication etiquette, has a significant impact on customer satisfaction, team harmony, and business image. The findings reveal that training in nonverbal communication and etiquette can enhance professionalism, customer loyalty, and team effectiveness. In addition, the visual design of culinary spaces also functions as a medium of nonverbal communication that strengthens brand identity. This study emphasises the importance of integrating communication training into human resource development in the culinary industry to meet the demands of professionalism and cultural diversity.